STRATEGI LAYANAN BIMBINGAN DAN KONSELING DALAM PENGEMBANGAN NILAI KARAKTER RELIGIUS - Nindiya Eka Safitri; Sitti Ummi Novirizka Hasan (STKIP Andi Matappa, 2018)
This article aims to describe the strategy of guidance and counseling services to development of the value of religious character. Character of religious desperately needed by the students to face the moral degradation, in order to they were able to have and behave with good and bad measure based on the provisions and statutes religion. The role of guidance and counseling as well as a service psychoeducative integral part of character education in schools is needed in the development of religious character. Strategy of guidance and counseling services that can be provided is a basic service such as the assessment of service needs, guidance classical, group counseling, and the use of innovative media; responsive service in the form of group counseling and individual counseling, as well as system support services in the form of collaboration between teacher guidance and counseling with religious teachers, religious leaders and parents, as well as the lack of research on the religious character by the teacher guidance and counseling. Religious character development do not all involve students but also pay attention to the surrounding environment and communities.